Heterosexual violence (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
In the same way that capitalism has required the slavery of indigenous and Afro-descendant populations to survive - using a racist ideologization that justifies the inferiority of non-Western societies -, patriarchy is based on the oppression and control of women through heterosexuality that is justified in the "nature" of sexual orientation (Rich, 1985). In this work, we reflect on the historical, cultural and ideological frameworks that have allowed the reproduction of violence not only against women, but above all, against lesbians. We also realize the need to make visible in a particular way these violences that go through the bodies, aesthetics and that justify social punishment on the deviation from the norm.Keywords: heterosexuality, heteropatriarchal, lesbian, violence.
Keywords: heterosexuality; heteropatriarchal; lesbian; violence